IMPROVING READING SKILL OF PROCEDURE TEXT TROUGH PICTURE WALK - Solihah, Ai; Rustandi, Ari (PROJECT (Professional Journal of English Education), 2020)
This study has a purpose at improving the reading skill in the topic “Procedure Text” of the students through Picture Walk. This research was a classroom action research conducted in two cycles, consisting of plan, implementation, observation or evaluation and reflection. The subjects of this study were 30 students of class VII A SMP Putra Juang Cianjur. There were 14 boys and 16 girls. The result of data analysis of the mean score of the first cycle was 67. Meanwhile, the mean score of the second cycle was 94.3. From the data, it can be said that the result of learning reading skill in the material “Procedure text using picture walk” in cycle I to cycle II has improved by 27.3. Based on the results of data analysis and discussion it can be concluded that the result of learning Reading Skill in the material “Procedure Text using Picture Walk”  can be improving Reading Skill on the students of class VII A SMP Putra Juang. It is recommended for English teachers to apply Reading skill using Picture Walk because it can improve the students’ achievement on Reading skill. Keywords:  Reading, procedure text, picture walk